Peran Guru dalam Menumbuhkembangkan Kesadaran Konstitusional di Daerah Tertinggal melalui Penghayatan Nilai-Nilai Luhur Pancasila - Fandi Setiawan (Universitas Negeri Medan, 2020)
The 1945 Constitution as the constitution of the Republic of Indonesia is the supreme law which serves as a guideline for lower laws and for state administrators and the wider community. The amendments to the 1945 Constitution were only limited to the achievement at the written constitution stage, not yet reached the living constitution stage. The constitution should begin to be implemented consistently and consistently. In fact, until now there is still a gap between the constitution on paper and the constitution in reality. The neglect and lack of understanding of the constitutional points still occur in real life including students in disadvantaged areas. To encourage the realization of students' understanding of constitutional awareness in the school, community, national and state environment, the Pancasila and Citizenship Education teachers can become parties who educate students to become children of the nation who have a culture of constitutional awareness through the appreciation of the noble values of Pancasila.